Contactless monitoring of respiratory rate variability in rats under anesthesia with a compact 24GHz microwave radar sensor - Sun, Guanghao; Kurosawa, Masaki; Ninomiya, Yoshiki; Baba, Kohei; Son, Nguyen Huu; Yen, Hoang Thi; Suzuki, Satoshi; Kano, Yutaka (Frontiers in Veterinary Science, 2025)
ObjectiveThe objective of this study was to develop and validate a noncontact monitoring system for respiratory rate variability in rats under anesthesia using a 24GHz microwave radar sensor. This study aimed to address the need for stress-free monitoring techniques that comply with the 3Rs principle (Reduction, Replacement, and Refinement) in laboratory animal settings.MethodsUtilizing a 24GHz microwave radar sensor, this system detects subtle body surface displacements induced by respiratory movements in anesthetized rats. The setup includes a 24.05 to 24.25 GHz radar module coupled with a single-board computer, specifically Raspberry Pi, for signal acquisition and processing. The experiment involved four male Wistar rats tracking the variability in their respiratory rates at various isoflurane anesthesia depths to compare the radar system’s performance with reference measurements.ResultsThe radar system demonstrated high accuracy in respiratory rate monitoring, with a mean difference of 0.32 breaths per minute compared to laser references. The Pearson’s correlation coefficient was high (0.89, p < 0.05), indicating a strong linear relationship between the radar and reference measurements. The system also accurately reflected changes in respiratory rates corresponding to different isoflurane anesthesia levels. Variations in respiratory rates were effectively mapped across different anesthesia levels, confirming the reliability and precision of the system for real-time monitoring.ConclusionThe microwave radar-based monitoring system significantly enhanced the animal welfare and research methodology. This system minimizes animal stress and improves the integrity of physiological data in research settings by providing a non-invasive, accurate, and reliable means of monitoring respiratory rates.